1989
DOI: 10.1210/endo-124-4-1727
|View full text |Cite
|
Sign up to set email alerts
|

Rat C6 Glial Cells Synthesize Insulin-Like Growth Factor I (IGF-I) and Express IGF-I Receptors and IGF-II/ Mannose 6-Phosphate Receptors*

Abstract: We have used the rat C6 glial cell line as a model system to study the role of insulin-like growth factors (IGF) in neuroglial cells of the central nervous system (CNS). Northern blot analysis of C6 RNA demonstrated the presence of IGF-I mRNA and undetectable IGF-II mRNA. IGF-I and IGF-binding protein(s), but not IGF-II, were detected in C6 glial cell-conditioned medium. The level of IGF-I was 1-4 ng/ml in conditioned medium based on a human IGF-I standard. The immunoreactive IGF-I inhibited [125I]IGF-I bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
2

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 40 publications
4
26
2
Order By: Relevance
“…2 depicts an autoradiogram from transfer blots of 10 ,g of total RNA of transfected and untransfected C6 and B-104 cells exposed to serum-free medium. The pattern of IGF-I transcripts in parental and transfected cells matches that published by us and others (6) showing prominent bands at 7.5, 1.8, and 1 kilobase (kb).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…2 depicts an autoradiogram from transfer blots of 10 ,g of total RNA of transfected and untransfected C6 and B-104 cells exposed to serum-free medium. The pattern of IGF-I transcripts in parental and transfected cells matches that published by us and others (6) showing prominent bands at 7.5, 1.8, and 1 kilobase (kb).…”
Section: Resultssupporting
confidence: 87%
“…We (5) and others (6) have reported that the rat glioma cell line C6 expresses high levels of insulin-like growth factor I (IGF-I), which is enhanced when grown in serum-free medium. Therefore, IGF-I expression may be coupled to cellular proliferation and tumorigenicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C6 cells are capable of producing IGF-I and releasing it into the culture medium [35]. Possibly, the autocrine secretion of IGF-I peptides by the cells may cause this densitydependent change in receptor number.…”
Section: Discussionmentioning
confidence: 99%
“…Serum-starved cells were incubated with MCDB 104 medium containing 0.1% BSA, 0.1 uM dexamethasone and 1 pg/ml transferrin (Furlanetto, 1988) to which was added serial dilutions of IGF-I, IGF-11, or DAP-1-treated IGF-11. After 22 hours, the cells were pulsed for one hour with [3H]thymidine and the monolayers were processed to determine the incorporation of radioactivity into trichloroaceticacid-precipitable material (Kiess et al, 1989).…”
Section: Incorporation Of ['Hlthymidine Into Dna In Mg-63 Cellsmentioning
confidence: 99%